THE CHARACTERISTICS OF ANTIDEPRESSANT AND ANTIANXIETY THERAPY IN OUTPATIENT PSYCHIATRIC PATIENTS AT RSKD DADI IN SOUTH SULAWESI 2024 - KEMAL, RAFIQAHAZZAHRA (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2026)
Mental health disorders, such as depression and anxiety, are common health issues in Indonesia, with a reported prevalence of 7%. The primary pharmacological treatments include antidepressants particularly selective serotonin reuptake inhibitors (SSRIs) and anxiolytics such as benzodiazepines. This study aims to examine the characteristics of antidepressant and anxiolytic therapy among outpatients at the Psychiatric Clinic of RSKD South Sulawesi Province in 2024, based on age, gender, drug class, and dosage. A descriptive cross-sectional observational design was employed through a review of medical records. Based on this approach, the study found that most patients were aged ≥50 years, with anxiety disorders more commonly diagnosed in males, while mixed disorders were more frequent in females. Benzodiazepines were the most prescribed (50%), followed by SSRIs (20%). The most common combination therapy was tricyclic antidepressants (TCAs) with benzodiazepines. Alprazolam was the most frequently prescribed medication. Although combination therapy is widely used, it requires careful monitoring due to the risk of dependency.